The Influence of Performance Assessment and Employee Abilities on Employee Career Development - Hasmawati Hasmawati; Winarti Winarti; Jumriani Jumriani; Muh. Akbardin; Amirah Kallabe (STIE Amkop Makassar, 2024)
This study examines the impact of performance assessment and workability on employee career development at PT Pelindo Terminal Petikemas New Makassar. The research utilized multiple linear regression analysis to assess the relationships between performance assessment, workability, and career development. Data were collected from a sample of employees at PT Pelindo Terminal Petikemas New Makassar and analyzed using t-tests and F-tests to determine the significance of the findings. The results indicate that performance assessment has a positive and significant influence on employee career development, while workability does not show a significant impact. Simultaneously, both performance assessment and workability account for 52.1% of the variance in career development, with the remaining 47.9% being influenced by other factors such as wages, job security, working conditions, achievements, training, and work experience. The findings align with theoretical frameworks in human capital theory and performance management, highlighting the importance of regular performance evaluations and skill enhancement. The study underscores the need for companies to prioritize performance assessment as a critical component of career development strategies. Organizations can foster a motivated and capable workforce by focusing on accurate performance evaluations and providing opportunities for skill development. Future research should explore additional variables affecting career development to provide a more comprehensive understanding and holistic recommendations for improving human resource management practices.